BARRIERS TO THE IMPLEMENTATION OF INTERNAL REGULATIONS OF RSUD DR. R.M DJOELHAM BINJAI IN REALIZING GOOD CLINICAL GOVERNANCE IN 2021 - OK Isnainul; Kartina Pakpahan (International Journal of Latin Notary, 2021)
The purpose of this study was to analyze: rules and regulations related to internal regulations in RSUD Dr. R.M. Djoelham Binjai, rules and regulations related to the implementation of good clinical service governance in Dr. RSUD. R.M. Djoelham Binjai, implementation of internal regulations of RSUD Dr. R.M. Djoelham Binjai in carrying out good clinical service governance. This type of research is a empirical juridical research using primary data and secondary data and data analysis carried out by qualitative methods. The results obtained: Regulations related to internal regulations at RSUD Dr. R.M. Djoelham Binjai is regulated in Binjai Mayor Regulation Number: 45 of 2018 concerning Hospital Internal Regulations (Hospital Bylaws) RSUD Dr. R.M. Djoelham City of Binjai which refers to the Decree of the Minister of Health Number: 772/MENKES/SK/VI/2002. The Decree of the Minister of Health of the Republic of Indonesia No.772/2002 was made based on the Law of the Republic of Indonesia Number: 23 of 1992 concerning Health; Law of the Republic of Indonesia Number: 22 of 1999 concerning Regional Government, Government Regulation Number: 32 of 1966 concerning Health Workers and Regulation of the Minister of Health of the Republic of Indonesia Number 159.b/1988 concerning Hospitals. RI Law Number: 23 of 1992 concerning Health has changed to RI Law Number: 36 of 2009 concerning Health while RI Law Number: 22 of 1999 concerning Regional Government has changed to RI Law Number: 23 of 2014 Regarding Regional Government while the Regulation of the Minister of Health of the Republic of Indonesia Number: 159.b/1988 concerning Hospitals has changed to Regulation of the Minister of Health of the Republic of Indonesia Number: 3 of 2020 concerning Hospital Classification and Licensing; Regulations related to the implementation of good clinical service governance in RSUD Dr. R.M. Djoelham Binjai refers to the Regulation of the Mayor of Binjai Number: 45 of 2018 concerning Hospital Internal Regulations (Hospital Bylaws) RSUD Dr. R.M. Djoelham City of Binjai as the highest person in charge for establishing hospital operational policies covering the fields of medical and nursing services, general and financial services, as well as human resources; Barriers to the implementation of internal regulations of RSUD Dr. R.M. Djoelham Binjai in carrying out good clinical service governance is a human resource because each individual has a different character when carrying out his duties and responsibilities.